Journalist Philosophy: Binding the Norms of Islamic Law - Datuk Imam Marzuki; Nasrillah; Mhd. Hasbi (Budapest International Research and Critics University, 2022)
Journalism is related to diaries that are published to the public and published in a certain way. Muslim journalism also breathes prophetic journalism, a form of journalism that not only reports news and problems in a complete, clear, honest, and actual way, but also provides interpretations and directions for change. ,transformation, based on the ethical and prophetic ideals of Islam. He became a journalism that consciously and responsibly contained the values and love of Islam. The philosophy of a journalist who is Muslim, ideally as a continuation of the Prophet's treatise is seen as an important study in today's information age. This is based on the view that the journalist is a teacher from the information society. then becomes important information that is absorbed by the public through the mass media. Because of his strategic position, he can become a benevolent spreader in the community through his mass media.